2018
DOI: 10.1038/s41598-018-19779-z
|View full text |Cite
|
Sign up to set email alerts
|

The ‘forma specialis’ issue in Fusarium: A case study in Fusarium solani f. sp. pisi

Abstract: The Fusarium solani species complex (FSSC) has been studied intensively but its association with legumes, particularly under European agro-climatic conditions, is still poorly understood. In the present study, we investigated phylogenetic relationships and aggressiveness of 79 isolates of the FSSC collected from pea, subterranean clover, white clover and winter vetch grown under diverse agro-climatic and soil conditions within Temperate and Mediterranean Europe. The isolates were characterized by sequencing te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…The Hypocreales contains species causing both human infections (only 64 out of 4479 described species) as well as major plant diseases, as an example of cross-kingdom pathogenicity (van Baarlen et al 2007;Segorbe et al 2017) or more accurately, crosskingdom opportunism. Other such examples include species of Fusarium, where both plant and human infection is frequent and strains have an unusually wide host range (Al-Hatmi et al 2016;Š išić et al 2018). Similarly, Sharma et al (2014) noted the plant-virulence of clinical strains of Exserohilum rostratum (Pleosporales), but this species is not host-specific, it has a wide host range on diverse grasses, and is also found in soil and on rotten materials (Ellis 1971).…”
Section: Extremotolerance and Opportunism Are Linked At The Level Of mentioning
confidence: 99%
“…The Hypocreales contains species causing both human infections (only 64 out of 4479 described species) as well as major plant diseases, as an example of cross-kingdom pathogenicity (van Baarlen et al 2007;Segorbe et al 2017) or more accurately, crosskingdom opportunism. Other such examples include species of Fusarium, where both plant and human infection is frequent and strains have an unusually wide host range (Al-Hatmi et al 2016;Š išić et al 2018). Similarly, Sharma et al (2014) noted the plant-virulence of clinical strains of Exserohilum rostratum (Pleosporales), but this species is not host-specific, it has a wide host range on diverse grasses, and is also found in soil and on rotten materials (Ellis 1971).…”
Section: Extremotolerance and Opportunism Are Linked At The Level Of mentioning
confidence: 99%
“…This suggested that additional genes might be required for better resolution within the species. Nevertheless, the classification and naming system of formae speciales within Fusarium species has been challenged with the discovery of polyphyly and the wide host range of a forma specialis (Pinaria et al , ; Šišić et al , ). In addition, the nomenclature of formae speciales lack standardization and some formae speciales even have multiple names (Edel‐Hermann and Lecomte, ).…”
Section: Discussionmentioning
confidence: 99%
“…lycopersici, F. keratoplasticum , and F. falciforme are known for their pathogenicity to plants, but have also been reported from humans and other mammals 1113. Similarly, F. pisi, F. temperatum, F. ramigenum, F. musae, Fusarium solani sensu stricto , and F. volatile have been recovered from living plants, while also their clinical relevance has been underlined 14,1921. Cross-kingdom pathogenicity is in obvious conflict with plant host specificity.…”
Section: Trans-kingdom Pathogenicitymentioning
confidence: 97%